Kearifan Lokal dalam siklus kehidupan manusia Nagakeo: Upaya pelestarian identitas budaya di tengah globalisasi - Mere, Klemens (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study examines the role of local wisdom in the life cycle of the Nagekeo people of Flores and its function as a foundation for preserving cultural identity amid globalization. Using a qualitative cultural approach, the research explores how traditional rituals—from birth to death—serve not only as symbols of spirituality but also as expressions of social cohesion and intergenerational continuity. Findings indicate that the Nagekeo community has adapted to the pressures of modernization and religion by integrating new meanings into long-standing traditions. Rituals that once centered on ancestral belief are now practiced alongside Christian values, creating a form of cultural synthesis that sustains both heritage and faith. Despite challenges such as commercialization and generational gaps, local wisdom remains a living framework guiding moral, social, and spiritual life. Thus, the preservation of cultural identity in Nagekeo demonstrates how tradition can coexist with modernity through creative adaptation and intergenerational participation.